Study of the Quality of Ground Waters of Some Villages at Shikohabad, District Firozabad (India) - Verma, Neelam; Pathak, Vishal; Yadav, D.C.; Pathak, Prabhat (Asian Journal of Chemistry, 2010)
The present paper destribes the results of a survey of the physicochemical characteristic of groundwaters of eight villages at Shikohabad, District Firozabad, U.P. over a period of one year. It can be concluded from this study that the pollutants in water of hand pumps are comparatively higher than the dugwells. Concentrations of chlorides, fluorides are within the limits as prescribed by WHO. On the other hand, nitrate-nitrogen, alkalinity and hardness are much higher. Entry of poilutants to the ground water is quite complex and several processes affect its movement.